Analyzing Success Factors of Enterprise Resource Planning Adoption using Analytical Hierarchy Process - Hawariyuni, Weni; Sentosa, Assoc. Prof. Dr. Ilham; Gadar, Assoc. Prof. Dr. Kamisan bin; Khrisnan, Dr. K Sarojini; Fatimah, Hilmi Azmi; Trisminingsih, Rina (International Journal of Innovation in Enterprise System, 2018)
Successful Enterprise Resorce Planning ERP system adoption in the company is one of the keys for the continuity of the company's business. On ERP adoption, there a lot of financials, time and human resources are invested on ERP adoption, so there must be an evaluation of ERP system to assess whether the ERP system adoption is successful or not. Some models have been developed by some researchers to assess the evaluation of ERP success. Each model has important factors used to assess the success of ERP. This study analyzes several factors that measure ERP success derived from several ERP success models to identify the important degree of each factor. The method used in this research is Analytical Hierarchy Process (AHP) with the assessment data obtained from 3 experts who have the competence and experience regarding ERP system. The results of this study found that the benefit of use, organizational impact, and user satisfaction are the 3 main subfactors with the highest important degree values. Keywords—Analytical Hierarchy Process, ERP success factors, ERP success model